PENGARUH LINGKUNGAN KERJA TERHADAP KUALITAS LAYANAN MASYARAKAT DENGAN KOMUNIKASI ORGANISASI SEBAGAI MEDIASINYA DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BULELENG - HARTAWAN, I GUSTI MADE DHARMA; ARYASARI, KADEK FLORESYA PUTRI (Ganec Swara, 2025)
This study aims to investigate whether the operational environments and communication within the organization impact the service quality at the Population and Civil Registrations Service of Buleleng Regency. Conducted within the service itself, the research encompassed all 56 employees. Utilizing a Likert scale for measurement, data was analyzed using the SEM PLS technique. Finding indicate that: 1) The operational environments positively and significantly influences service quality at the Buleleng Regency Population and Civil Registration Service. 2) The operational environment also positively and significantly affects organizational communication within the service. 3) Organizational communication demonstrates a positive and significants impact on service quality at the service. 4) The operational environment directly affects community service quality, with organizational.